2018
DOI: 10.14295/ras.v32i3.29137
|View full text |Cite
|
Sign up to set email alerts
|

Trapeamento de LNAPL observado por meio da técnica de fluorescência induzida por laser (LIF)

Abstract: Modelos conceituais de áreas contaminadas são, em geral, os primeiros resultados significativos do gerenciamento ambiental. Contudo, é necessário entender a complexidade dos meios contaminados para que seja adotada a melhor alternativa de remediação. A distribuição espacial em subsuperfície da fase liquida não aquosa menos densa que a água (LNAPL – Light Non-Aqueous Phase Liquid), geralmente de elevada variabilidade espacial e, consequentemente, complexa, deve ser mais bem conhecida. Além disso, a flutuação sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
0
3
0
16
Order By: Relevance
“…Teramoto and Chang [46] demonstrated that the water table fluctuations in the aquifer studied have high amplitudes, favoring the entrapment of LNAPL. Isler et al [21] verified that most of the LNAPL is distributed as an entrapped phase nearly 2 m below the water table via the use of laser-induced fluorescence (Figure 2), as a result of strong water table fluctuations recorded in the field. As demonstrated by Teramoto and Chang [15], the concentrations of BTEX in the aqueous phase are directly related to the concentrations in the LNAPL.…”
Section: Case Studymentioning
confidence: 96%
See 2 more Smart Citations
“…Teramoto and Chang [46] demonstrated that the water table fluctuations in the aquifer studied have high amplitudes, favoring the entrapment of LNAPL. Isler et al [21] verified that most of the LNAPL is distributed as an entrapped phase nearly 2 m below the water table via the use of laser-induced fluorescence (Figure 2), as a result of strong water table fluctuations recorded in the field. As demonstrated by Teramoto and Chang [15], the concentrations of BTEX in the aqueous phase are directly related to the concentrations in the LNAPL.…”
Section: Case Studymentioning
confidence: 96%
“…In tropical and subtropical climates, the amplitude of the water table fluctuation is typically high [15,20]. Under these conditions, the LNAPL may be completely entrapped below the water table, as described by Isler et al [21]. The release of soluble compounds into the water from LNAPL comprises a multicomponent mixture (e.g., gasoline, jet fuel, diesel) and occurs because of the limited rate mass transfer phenomenon (non-equilibrium condition).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A despeito de métodos de varredura (screening) vertical de SQIs (como Membrane Interface Probe -MIP, métodos Laser-Induced Fluorescence -LIF, entre outros) serem muito importantes e úteis na investigação (ROSSI e PITKIN, 2014;McCALL et al, 2014;SUTHERSAN et al, 2015;ISLER et al, 2018;RIYIS et al 2015a;RIYIS, 2018), não se pode prescindir de amostras de solo para análises químicas em laboratório, de acordo com a DD-038. Os métodos de varredura auxiliam no entendimento da distribuição da massa de SQI no meio e na seleção das amostras a serem encaminhadas ao laboratório, mas não substituem as análises quantitativas.…”
Section: Delimitação E Quantificação De Massa No Solounclassified
“…Muitos estudos, dentre os quais se destacam Guilbeault et al (2005) Guilbeault et al (2005) mostrou que, mesmo em meios homogêneos, pontos de amostragem de água subterrânea distantes verticalmente mais de 30 cm não conseguem determinar adequadamente a distribuição vertical dos contaminantes em fase dissolvida. Einarson et al (1999) chegaram na distância máxima de 45 cm entre um ponto de amostragem e outro, também em meio homogêneo.…”
Section: Unidades Hidroestratigráficasunclassified